2013
DOI: 10.2478/bpasts-2013-0066
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of polycaprolactone/gelatin blends in terms of their miscibility

Abstract: Abstract. Synthetic and natural polymers blends represent a new brand of materials with application in wound healing, scaffolds or drug delivery systems. Polycaprolactone/gelatin (PCL/Gt) blends were analyzed in terms of their miscibility. The PCL structure was investigated as a function of Gt content. Changes in the PCL spherulitic structure with Gt content were investigated by a polarizing-interference microscope. The analysis of the glass transition temperature (Tg) of both components as a function of PCL/G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 14 publications
2
23
0
1
Order By: Relevance
“…Poor evidence of substance peaks due to a small amount of this substance in different systems had been previously reported [35]. for all samples (PLC bulk, PCL nanofibers, and BIOG PCL nanofibers) [36,37]. The incorporation of BIOG nanoparticles into the polymeric nanofibers did not affect significantly the semicrystalline nature of the PCL and the volume fraction of PCL crystals within the material (since both the melting point and enthalpy of melting are similar for all samples).…”
Section: Resultsmentioning
confidence: 58%
“…Poor evidence of substance peaks due to a small amount of this substance in different systems had been previously reported [35]. for all samples (PLC bulk, PCL nanofibers, and BIOG PCL nanofibers) [36,37]. The incorporation of BIOG nanoparticles into the polymeric nanofibers did not affect significantly the semicrystalline nature of the PCL and the volume fraction of PCL crystals within the material (since both the melting point and enthalpy of melting are similar for all samples).…”
Section: Resultsmentioning
confidence: 58%
“…The immiscibility of PCL and gelatin occurs due to the sol–gel transition, which has already been reported . Increasing the PCL content in the blend resulted in greater immiscibility demonstrated as beaded fibres from 70:30 gelatin‐to‐PCL composition which led to greater non‐homogeneity in the fibre diameter distribution .…”
Section: Resultsmentioning
confidence: 61%
“…A blend of 70:30 gelatin‐to‐PCL composition facilitated the formation of homogeneous and continuous cartilage . Kolbuk et al observed a gelatin‐to‐PCL ratio of 80:20 to be a one‐phase structure, reaching intermediate miscibility caused by the strong interactions between gelatin and PCL . Smoother fibres were obtained with the 80:20 gelatin‐to‐PCL blend in our case, and therefore it was selected as the optimized blend composition for further experimentation.…”
Section: Resultsmentioning
confidence: 71%
“…The higher T g of PGSu in blends suggest changes in the mobility of oligomer chains, which might be related to good oligomer distribution [32] and/or the compatibility of both components. The T g shift of the bicomponent fibre components towards each other observed in PLLA with PGSu (PLLA10, PLLA20) indicates polar interactions and compatibility between both polymers [4,33]. Mesophase formation in bicomponent fibres with PLLA was detected with WAXS, which proves its better chain mobility due to the PGSu additive.…”
Section: Discussionmentioning
confidence: 86%